Review of the book The Thriving Adolescent - Brandão, Luiza Chagas (Perspectivas em Análise do Comportamento, 2019)
The book The Thriving Adolescent describes a psychotherapy model to be used with young people. It is based on both Acceptance and Commitment Therapy and Positive Psychology. This review presents the DNA-V model and briefly discusses its contributions to behavior analytic therapists.